Nicaragua : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
This Poverty Reduction Strategy Paper for Nicaragua reports that the most pressing demand for the majority of Nicaraguans is employment generation and economic growth. The National Development Plan (NDP) gives priority to actions that improve the investment climate and promote productive development-considering the competitive potential of the territories-giving a better position to Nicaragua in the trading world through increased foreign investment. The NDP establishes a more effective regulatory framework, and promotes competition and a legal framework that guarantees property rights and lowers domestic transaction costs.